Structure design and optimization of SOI high-temperature pressure sensor chip. (December 2021) - Tang, Xin; Tian, Junwang; Zhao, Jiafeng; Jin, Zhong; Liu, Yunpeng; Liu, Junfu; Chen, Taotao; Li, Junhui
Abstract: A high-temperature pressure sensor chip based on SOI(Silicon-On-Insulator) material is designed in this paper. In this paper, the structural design of the elastic pressure-sensitive diaphragm is carried out, and the diaphragm dimensions are optimized using finite element analysis, according to the sensor's Wheatstone bridge principle and hydrostatic simulation method, combined with the sensor's design requirements. The optimal design dimensions of the elastic pressure-sensitive diaphragm at 2.1 MPa pressure were finally determined, with an island width w1 of 600 μm, a membrane length of w2 of 1000 μm, a membrane thickness h1 of 60 μm, and an island height h2 of 440 μm. Under the premise of 5KΩ varistor value, the packaging structure and process of the sensor are designed to finally obtain the test results that meet the initial setting value.